2018
DOI: 10.5812/archcid.65512
|View full text |Cite
|
Sign up to set email alerts
|

First Report of the Prevalence of Human T-Lymphotropic Virus Type 1 (HTLV-1) for Hemodialysis Patients in Tehran

Abstract: Background: Human T-lymphotropic virus type 1 (HTLV-1) virus belongs to retroviruses and is involved in the etiology of adult T-lymphocytic leukemia (ATL) and tropical spastic paraparesis (TSP). This virus could be transmitted through transfusion of contaminated blood or blood products, from the mother to the child or fetus, sexual intercourse, and sharing contaminated syringe needles among addicted individuals. There is no report regarding the prevalance of HTLV-1 among hemodialysis patietns in Tehran. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…On the other hand, HTLV-1 infection is expected to have a lower prevalence among HD patients from non-endemic parts of Iran. A study performed in Tehran among HD patients (24 to 88 years old) showed that the prevalence of HTLV-1 was 0.66% (one positive case among 150 patients) (11). In a study conducted in Mazandaran, an area with very low incidence of HTLV-1 infection in north of Iran (12), only 0.6% of HD patients showed seropositivity for this infection (13).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, HTLV-1 infection is expected to have a lower prevalence among HD patients from non-endemic parts of Iran. A study performed in Tehran among HD patients (24 to 88 years old) showed that the prevalence of HTLV-1 was 0.66% (one positive case among 150 patients) (11). In a study conducted in Mazandaran, an area with very low incidence of HTLV-1 infection in north of Iran (12), only 0.6% of HD patients showed seropositivity for this infection (13).…”
Section: Discussionmentioning
confidence: 99%